Identification of mitophagy-related biomarkers with immune cell infiltration in psoriasis - Shanshan Yu; Fangyuan Long; Hui Yan; Yongfang Xu; Jun Li; Zhimin Hao (BMC Medical Genomics)
Abstract Background Psoriasis is an inflammatory disorder characterized by scaly erythematous plaques and significant comorbidities. Recent studies have suggested that impaired mitophagy, the cellular mechanism for removing dysfunctional mitochondria, may contribute to the pathogenesis of psoriasis. Methods In this study, we analyzed bulk RNA sequencing data from 167 healthy individuals and 177 patients with psoriasis obtained from the Gene Expression Omnibus database (GSE30999 and GSE54456). Mitophagy-related genes were isolated using weighted gene co-expression network analysis. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed and protein-protein interaction networks were constructed for the functional enrichment of genes associated with mitophagy. The correlations between genes associated with mitophagy, signaling pathways, and immune cell infiltration were analyzed. The potential diagnostic value of genes associated with mitophagy was evaluated using receiver operating characteristic (ROC) curves, which were validated in imiquimod-induced psoriatic skin lesions in mice. Results We identified 3,839 differentially expressed genes between healthy individuals and patients with psoriasis, and 23 genes were selected as hub genes showing a high correlation with mitophagy in psoriasis. GO and KEGG analyses revealed that hub and associated genes were significantly correlated with skin functions, such as epidermal development and keratinocyte differentiation. In addition, mitophagy-related genes were negatively associated with pro-inflammatory and pro-proliferation pathways in psoriasis. Among the immune cells, CD4+ T cells were most significantly affected by mitophagy-related genes. ROC analysis demonstrated that mitophagy-related genes, especially ACER1, C1ORF68, CST6, FLG2, GJB3, GJB5, GPRIN2, KRT2, and SPRR4 were potential biomarkers of psoriasis for use in diagnosis or treatment. Conclusions Mitophagy-related genes play crucial roles in psoriasis and have potential use as biomarkers, providing insights into disease mechanisms and therapeutic targets. Further research may lead to the development of new strategies for psoriasis management.